Purchasing Power : Black Kids and American Consumer Culture - Chin, Elizabeth, 1963- (Book collections on Project MUSE., 2001)
What does it mean to be young, poor, and black in our consumer culture? Are black children "brand-crazed consumer addicts" willing to kill each other over a pair of the latest Nike Air Jordans or Barbie backpack? In this first in-depth account of the consumer lives of poor and working-class black children, Elizabeth Chin enters the world of children living in hardship in order to understand the ways they learn to manage living poor in a wealthy society